2007
DOI: 10.1080/13682820600783178
|View full text |Cite
|
Sign up to set email alerts
|

Language impairments in sign language: breakthroughs and puzzles

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 15 publications
1
40
0
5
Order By: Relevance
“…Siegel and Ryan (1988), for example, found that children with learning disabilities performed significantly more poorly than typically developing children on grammatical error correction tasks. The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, 2014;Marshall et al, 2014;Mason et al, 2010;Morgan, Herman, & Woll, 2007;Woll & Morgan, 2012) and ASL Quinto-Pozos et al, 2013, Quinto-Pozos, Forber-Pratt, & Singleton, 2011. These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers' scores should be compared to nonnative norms and native signers' scores should be compared to native norms (Herman, Holmes, & Woll, 2001;Mann & Marshall, 2012).…”
Section: Additional Learning Disabilities Affect Primarily the Performentioning
confidence: 59%
“…Siegel and Ryan (1988), for example, found that children with learning disabilities performed significantly more poorly than typically developing children on grammatical error correction tasks. The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, 2014;Marshall et al, 2014;Mason et al, 2010;Morgan, Herman, & Woll, 2007;Woll & Morgan, 2012) and ASL Quinto-Pozos et al, 2013, Quinto-Pozos, Forber-Pratt, & Singleton, 2011. These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers' scores should be compared to nonnative norms and native signers' scores should be compared to native norms (Herman, Holmes, & Woll, 2001;Mann & Marshall, 2012).…”
Section: Additional Learning Disabilities Affect Primarily the Performentioning
confidence: 59%
“…Morgan, Herman and Woll (2007) reported the case of a deaf five year-old boy with SLI in British Sign Language (BSL). He had no difficulty in understanding single signs and short sentences, but he scored at a three-year-old level on standardized BSL grammar assessments.…”
mentioning
confidence: 99%
“…Sign language researchers have begun to explore the presence of specific sign language disorders in deaf children (Mason et al, 2010;Morgan et al, 2007;Quinto-Pozos et al, 2011). These initial efforts make use of survey and case study approaches to examine a small number of deaf children, who despite having deaf signing parents, have been identified by teachers as having atypical problems in signing.…”
Section: Sign Language-specific Deficitsmentioning
confidence: 99%
“…In one example, Morgan et al (2007) reported the case of Paul, a 5-year-old native deaf signer of BSL with a sign language impairment which they entertain as a possible analogue of specific language impairment (SLI) evidenced in a sign language. SLI is diagnosed where a deficit in normal spoken language acquisition is found with no apparent cognitive, social, or neurological cause (Leonard, 1998).…”
Section: Sign Language-specific Deficitsmentioning
confidence: 99%